Indazole, Pyrazole, and Oxazole Derivatives Targeting Nitric Oxide Synthases and Carbonic Anhydrases. (5th July 2016) - Maccallini, Cristina; Di Matteo, Mauro; Vullo, Daniela; Ammazzalorso, Alessandra; Carradori, Simone; De Filippis, Barbara; Fantacuzzi, Marialuigia; Giampietro, Letizia; Pandolfi, Assunta; Supuran, Claudiu T.; Amoroso, Rosa
Abstract: Nitric oxide (NO) is an essential endogenous mediator with a physiological role in the central nervous system as neurotransmitter and neuromodulator. A growing number of studies have demonstrated that abnormal nitrergic signaling is a crucial event in the development of neurodegeneration. In particular, the uncontrolled production of NO by neuronal nitric oxide synthase (nNOS) is observed in several neurodegenerative diseases. Moreover, it is well recognized that specific isoforms of human carbonic anhydrase (hCA) physiologically modulate crucial pathways of signal processing and that low expression of CA affects cognition, leading to mental retardation, Alzheimer′s disease, and aging‐related cognitive impairments. In light of this, dual agents that are able to target both NOS (inhibition) and CA (activation) could be useful drug candidates for the treatment of Alzheimer′s disease, aging, and other neurodegenerative diseases. In the present work, we show the design, synthesis, and in vitro biological evaluation of new nitrogen‐based heterocyclic compounds. Among the tested molecules, 2‐amino‐3‐(4‐hydroxyphenyl)‐ N ‐(1 H ‐indazol‐5‐yl)propanamide hydrochloride (10 b ) was revealed to be a potent dual agent, able to act as a selective nNOS inhibitor and activator of the hCA I isoform. Abstract : Double agent ! This study involved the design, synthesis, and in vitro biological evaluation of a cluster of new nitrogen‐based heterocyclic compounds. Compound10 b was revealed to be a potent dual agent, able to act as a selective neuronal nitric oxide synthase inhibitor and activator of the human carbonic anhydrase I isoform. It is a promising lead for the design of therapies for neurological diseases.